DETERMINASI PELATIHAN, MOTIVASI, GAJI, DAN KOMPENSASI UNTUK PRODUKSI (STUDI KASUS PADA CV ANUGRAH WALET INDONESIA) - Andika Arianto; Abid Muhtarom; Haris Bashory Ismail; Ruswaji Ruswaji; Henny Mahmudah (Universitas Muhammadiyah Sorong, 2018)
Studied, salary has a dominant influence on productivity in CV. Anugrah Walet Indonesia. Economic growth in Indonesia is very rapid and causes the competition of the market is getting tighter. This study aims to determine the determination of training, motivation, salary, and compensation for CV production. Anugrah Walet Indonesia.This research uses descriptive method, in qualitative form using Probability Sampling technique. The sample of this research is 40 employees. This research uses validity test, reability, classical assumption, multiple linear regression, coefficient of determination, t test, and f test. This study uses EVIEWS 9 program. Partially there is significant influence between training, motivation, salary, and compensation to production at CV. Grace swallowed Indonesia. Simultaneously there is a significant influence between training, motivation, salary, and compensation on production in CV. Grace swallowed Indonesia. Among the 4 independent variables salary has a dominant influence on productivity on CV. Anugrah Walet Indonesia